Computer anxiety its determinants and its relationship to library anxiety - Salvador, Ma. Criselda R. (Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The study is concerned with determining if the independent variables - age, sex, course, type of computer experience, pleasantness/unpleasantness of computer experience, reason for computer use, frequency of student's library use, frequency of computer use in the library and frequency of computer use outside the library-influence the level of computer anxiety and library anxiety of the U.P. students.